Facile fractionation of lignocelluloses by biomass-derived deep eutectic solvent (DES) pretreatment for cellulose enzymatic hydrolysis and lignin valorization - Shen, Xiao-Jun; Wen, Jia-Long; Mei, Qing-Qing; Chen, Xue; Sun, Dan; Yuan, Tong-Qi; Sun, Run-Cang (Green chemistry : an international journal and green chemistry resource : GC, 2019)
A low-cost and green biorefinery will increase the economy and revenue from lignocellulosic biomass. Herein, a biomass-derived deep eutectic solvent (DES) pretreatment was developed to deconstruct the recalcitrant structure of Eucalyptus for further cellulose enzymatic hydrolysis and lignin valorization. The DES consisted of biomass-derived chemicals (lactic acid and choline chloride). The results showed that DES pretreatment resulted in notable removal of hemicelluloses and lignin, and drastically reduced “biomass recalcitrance”. Under the optimum conditions (DES ratio: 10 : 1, temperature: 110 °C, time: 6 h), the glucose yield by enzymatic hydrolysis reached 94.3%, which was significantly enhanced 9.8 times compared to that of the original biomass without DES pretreatment. The state-of-the-art analysis indicated that the regenerated lignin exhibited well-preserved structures ( i.e. , β- O -4, β–β linkages) without contaminated carbohydrates, and it had a relatively low and homogeneous molecular weight. All these structural characteristics suggested that lignin has great potential application in its conversion into bio-based chemicals and materials. Besides, it is urgent to develop low-cost recycled DESs as green solvents for sustainable biomass pretreatment. The lifetime and recyclability experiment of the DES solution showed that the recovery yield of the DES was at least 90% and the fundamental structural properties of the recycled DES were almost unchanged throughout the recycling cycles. More importantly, the pretreatment efficiency (delignification and enzymatic saccharification) was still largely maintained after the recycling process. Overall, this work demonstrated that biomass pretreatment with the recycled DES was promising for a low-cost biorefinery to achieve an efficient fractionation of lignocellulosic biomass into fermentable glucose and high-quality lignin with tailored chemical structures.